Analisis Tugas dan Fungsi Penyidik Pegawai Negeri Sipil (PPNS) Balai Konservasi Sumber Daya Alam Lampung Terhadap Tindak Pidana Satwa Liar yang di Lindungi - Benny Karya Limantara (PRANATA HUKUM, 2015)
Natural resources and ecosystem of Indonesia plays an important role for the life in the present and future development of natural resources and its ecosystem is an integral part of national sustainable development as the implementation of Pancasila. The problem in this research is how the implementation of the duties and functions of Civil Servant Investigators Lampung BKSDA in offenses wildlife. Based on the research and discussion, it was stated that the duties and functions of civil servant investigators BKSDA Lampung in offenses wildlife is protected in accordance with provisions stipulated in the Criminal Procedure Code and Act No. 5 of 1990, this means that investigators with the authority as investigators have a legal obligation, namely; (1) notify and report on the investigations conducted by the Police as investigators report the commencement of the investigation, (2) inform the development of the investigations conducted by the Police Investigator, (3) may ask for guidance and assistance as needed investigation, (4) notify the termination of the investigation is done, (5) submit the case file, the suspect and the evidence to the Public Prosecutor through the Police Investigators.